Pengaruh Pendidikan Kesehatan terhadap kemampuan Perawatan Payudara pada Ibu Hamil Trimester III - Niswatun Niswatun; Ika Agustina (Journal of Ners and Midwifery, 2015)
Good treatment of breast after both during pregnancy and maternity,will keep the form of breast and will also affect the breastmilk. Method: The design was pre experimental. The population in this research were 20 pregnant woman trimester III in the Polindes Village Kecamatan Kanigoro Kabupaten Blitar. Samples in this research were 15 pregnant women trimester III in the polindes village brass Kecamatan Kanigoro Kabupaten Blitar. the sampling technique used purposive sampling. The research were Conducted on 4–7 April 2015 in polindes village Kuningan Kecamatan Kanigoro Kabupaten Blitar. This statiscal test used wilcoxon rank test using SPSS for window. Result: The result showed that 80% of respondents were not enough to do breast care in before the treatment and 80% of respondents can do breast care after the treatment. Based on wilcoxon statistical test, the value was 0,000. This showed that there was an effect of education and health care of the mother breast ability in polindes desa Kuningan kecamatan kanigoro Kabupaten Blitar. Discussion: It was suggested for pregnant women on third trimester will be able to perform breast care with the correct methods and techniques, since breast care is very important for the preparation breastfeeding at birth.